2011
DOI: 10.1523/jneurosci.2859-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Object-in-Place Learning in Hippocampus and Prefrontal Cortex

Abstract: Hippocampus and prefrontal cortex (PFC) process spatiotemporally discrete events while maintaining goal-directed task demands. Although some studies have reported that neural activities in the two regions are coordinated, such observations have rarely been reported in an object-place paired-associate (OPPA) task in which animals must learn an object-in-place rule. In this study, we recorded single units and local field potentials simultaneously from the CA1 subfield of the hippocampus and PFC as rats learned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 50 publications
1
98
0
Order By: Relevance
“…As used here, PAL involves the encoding and retrieval of object-location information. Performance in this task may be linked to hippocampal and prefrontal cortical function as shown in rats (Kim et al 2011;Talpos et al 2014) and humans studies (de Rover et al 2011;Hales et al 2009;Owen et al 1995) using a similar paired associate learning task. Surprisingly, NVP-AAM077 did not show improvement or impairment on this task, especially as MK-801 produced robust impairments in PAL.…”
Section: Discussionmentioning
confidence: 96%
“…As used here, PAL involves the encoding and retrieval of object-location information. Performance in this task may be linked to hippocampal and prefrontal cortical function as shown in rats (Kim et al 2011;Talpos et al 2014) and humans studies (de Rover et al 2011;Hales et al 2009;Owen et al 1995) using a similar paired associate learning task. Surprisingly, NVP-AAM077 did not show improvement or impairment on this task, especially as MK-801 produced robust impairments in PAL.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with this hypothesis is the observation that disconnection lesions of the PFC and inferotemporal cortex in monkeys impair delayed nonmatching-to-sample performance (Browning, Baxter, and Gaffan, 2013) and object-in-place scene memory (Wilson, Gaffan, Mitchell, and Baxter, 2007). Additional evidence for a unified mPFC-PER network that supports performance on the OPPA task is that the theta rhythm in the mPFC and hippocampus becomes more synchronized after acquisition of the OPPA task rule (Kim, Delcasso, and Lee, 2011). Because there are limited direct projections from mPFC to dorsal hippocampus, this synchrony may require that information flows through the rhinal cortices, thus making the PER an integral part of this circuit.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wood et al (108) showed that different subsets of neurons selectively coded for "what" (e.g., a specific odor) and "where" (e.g., a specific location) information whereas others coded for specific what-where conjunctions (a specific odor in a particular place). More recent studies have shown that the emergence of what-where coding parallels the learning of item-place associations (109,110). Although lesions studies suggest what-where integration depends on subregion CA3 but not CA1 (34), what-where neural coding has been reported in both subregions with no significant differences reported (108,109).…”
Section: Neural Mechanisms Underlying Episodic Memorymentioning
confidence: 97%